MEDIATION AS A TOOL FOR WORKPLACE CONFLICT MANAGEMENT: INTERNATIONAL EXPERIENCE AND PROSPECTS FOR UKRAINE - Акіліна, Олена (SWorldJournal, 2025)
The article explores mediation as a modern tool for workplace conflict management that is gaining strategic importance in the context of increasingly complex employment relations. The introduction substantiates the relevance of the topic, emphasizing the